Problem Analysis and Manual Warehouse System Improvement Strategy Towards Smart & Sustainable Warehouse - Annisa Syarifa; Tukhas Shilul Imaroh (International Journal of Indonesian Business Review, 2026)
Conventional warehouse management systems are still widely applied in the construction and heavy manufacturing industries in Indonesia, including at PT ABC which is engaged in the fabrication of steel bridges. This research aims to analyze the main problems in the conventional warehouse system in the company and provide recommendations for improvement towards a smart & sustainable warehouse system. The research method used is qualitative case study, with data collection techniques through observation, in-depth interviews, Focus Group Discussions (FGD), and documentation. The analysis techniques used include Root Cause Analysis and the 5W1H approach. The results of the study showed a number of systemic weaknesses, such as the absence of a dedicated warehouse admin, the absence of a labeling system, the weak implementation of Standard Operating Procedures (SOPs), and an inefficient warehouse layout. This study recommends five steps for improvement: (1) appointment of special warehouse admins, (2) activation of labeling and Bin Card systems, (3) consistent enforcement of SOPs, (4) implementation of barcode systems, and (5) rearrangement of zoning-based warehouse layouts. This change effort is expected to improve warehouse operational efficiency and support the principles of Sustainable Supply Chain Management (SSCM) in the framework of industry 4.0.